Brainstem Correlates of Speech-in-Noise Perception in Children - Anderson, Samira (2010)
Children often have difficulty understanding speech in challenging listening environments. In the absence of peripheral hearing loss, these speech perception difficulties may arise from dysfunction at more central levels in the auditory system, including subcortical structures. We examined brainstem encoding of pitch in a speech syllable in 38 school-age children. In children with poor speech-in-noise perception, we find impaired encoding of the fundamental frequency and the second harmonic, two important cues for pitch perception. Pitch, an important factor in speaker identification, aids the listener in tracking a specific voice from a background of voices. These results suggest that the robustness of subcortical neural encoding of pitch features in time-varying signals is an important factor in determining success with speech perception in noise.